Ab initio study of electronic structures of BaMoO4 crystals containing an interstitial oxygen atom - Zhao, H.; Zhang, Feiwu; Guo, X.; Zhang, Q.; Liu, T. (Elsevier Science Limited, 2010)
The electronic structures of the perfect BaMoO4 and BaMoO4 crystals containing an interstitial oxygenatom situated at an appropriate position with the total energy being the lowest are studied within the framework of the density functional theory with the lattice structure optimized. The calculated results reveal that the interstitial oxygen atom situated at two different interstitial sites would combine with formal lattice oxygen ions forming molecular ions in two different ways, and the interstitial oxygenatom would cause visible range absorption band peaked at about 320nm.